PASJA I TOŻSAMOŚĆ NAUKOWCA - Melosik, Zbyszko (Rocznik Pedagogiczny, 2018)
The aim of the article is to analyse various contexts of passion perceived as an important com- ponent of researcher’s identity. First, passion is confronted with the concept if rationality which dominates the university thinking about research. Second, passion is considered in relations to in- trinsic and extrinsic motivation. Next, the author concentrates attention on factors which limit the passion development: present commercialization of research as well as their permanent indexation and evaluation, re-locating the researcher’s energy on permanent reporting and detailed juridization of academic reality. At the end the possibility of passion in contemporary research is optimistically confirmed by the idea of academic community and academic freedom.